Impact of collagen-induced arthritis on the pharmacokinetic disposition of voriconazole, a widely used antifungal agent: in vitro and in vivo investigations in DBA/1J mice. (3rd June 2019) - Giri, Poonam; Delvadia, Prashant; Gupta, Lakshmikant; Trivedi, Priyal; Patel, Nirmal; Sharma, Manoranjan; Singh, Jaideep; Chatterjee, Abhijit; Kadam, Shekhar; Srinivas, Nuggehally R.
Abstract: Pharmacokinetics of voriconazole, an anti-fungal agent, was determined in collagen-induced arthritic (CIA) and healthy DBA/1J mice. CIA was confirmed in DBA/1J mice by clinical scoring and histological analysis. In vivo oral pharmacokinetic study (3 mg/kg) and in vitro stability assessment in liver microsomes were performed in CIA vs. healthy DBA/1J mice. Additionally, hepatic portal vein cannulated (HPVC) CIA and healthy mice were used to clarify the role of gut first-pass effect. Voriconazole/N-oxide metabolite was measured in plasma and in vitro samples using liquid chromatography tandem-mass spectrometry method. Voriconazole exposure was reduced in CIA by 27% as compared to healthy mice. Formation of voriconazole N-oxide was higher in CIA mice as evidenced by higher molar Cmax ratio (i.e. metabolite/parent) of 2.08 vs. 1.66 in healthy mice. Because voriconazole was stable in microsomes, involvement of presystemic gut metabolism was suspected for decreased voriconazole exposure and formation of higher molar ratio of metabolite. HPVC work revealed higher formation of voriconazole N-oxide in CIA relative to healthy mice resulting in Cmax /AUC ratios of 0.41/0.54 and 0.08/0.17, respectively, confirming first-pass effect. The findings may have implications in the clinical therapy of arthritis patients who are concomitantly given voriconazole for the management of fungal infections.